2006
DOI: 10.1007/s00726-006-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood amino acids concentration during insulin induced hypoglycemia in rats: the role of alanine and glutamine in glucose recovery

Abstract: Our purpose was to determine the blood amino acid concentration during insulin induced hypoglycemia (IIH) and examine if the administration of alanine or glutamine could help glycemia recovery in fasted rats. IIH was obtained by an intraperitoneal injection of regular insulin (1.0 U/kg). The blood levels of the majority of amino acids, including alanine and glutamine were decreased (P < 0.05) during IIH and this change correlates well with the duration than the intensity of hypoglycemia. On the other hand, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
2
24
0
2
Order By: Relevance
“…Our previous study 9) demonstrated that the blood concentrations of L-alanine and L-glutamine were decreased during long term IIH. In agreement with this study, 9) we also demonstrated that oral glutamine dipeptide was able to promote glycemia recovery during long term IIH.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our previous study 9) demonstrated that the blood concentrations of L-alanine and L-glutamine were decreased during long term IIH. In agreement with this study, 9) we also demonstrated that oral glutamine dipeptide was able to promote glycemia recovery during long term IIH.…”
Section: Discussionmentioning
confidence: 90%
“…4) However, there are few studies in the prevention of nocturnal hypoglycemia. 5,6) Because rats show a suitable experimental model to study hypoglycemia [7][8][9][10] and considering the night habits of these animals, nocturnal IIH can be simulated with a diurnal pharmacological dose of Detemir insulin. Moreover, in spite the fact that glutamine dipeptide has been shown effective to promote acute glycemia recovery during long term IIH, 11) its rule to prevent prolonged hypoglycemia was not investigated.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to remember that this conclusion data cannot easily be related to clinical practice, since L-glutamine is not stable in aqueous solution and its oral administration during short-term IIH did not promote glycaemia recovery probably as consequence of its intense catabolism by the enterocytes. 22,25,28 Furthermore, the present results suggest that to prevent hypoglycaemia, L-lactate or glycerol remain more efficient than L-glutamine, whether in COG or IIH weaned rats.…”
Section: Discussionmentioning
confidence: 51%
“…This experimental approach discards the influence of hepatic glycogen catabolism, changes in the hepatic blood flux and the variability of blood glucose precursors. 5,12 In contrast with adult hypoglycaemic rats in which the liver glucose production from L-alanine and L-lactate were increased, 22 the glucose production from these gluconeogenic substrates in livers from weaned hypoglycaemic rats was not affected by short-term IIH. On the other hand, like adult rats, 23,24 gluconeogenesis from L-glutamine which enters in this metabolic pathway after the pyruvate carboxylase step and before the phosphoenolpyruvate carboxykinase step 25 markedly rise in livers from shortterm IIH weaned rats.…”
Section: Discussionmentioning
confidence: 97%